Motivasi Keagamaan Konsumen Muslim Dalam Penggunaan Bank Syariah - Fattah Setiawan Santoso (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2020)
The study of the rationality of consumption behavior in choosing Islamic banking can use many frameworks of thought, but the writing of this paper is devoted to the use of an Islamic economic philosophy framework based on the Quran because its object is the issue of religious obedience as a reason for Muslim consumers to choose Islamic banking. His study is focused on the interpretation of the verses of the Koran regarding the consumption behavior of the perpetrators. This behavioral study is then used to analyze consumer tendencies towards the existence of usury by switching to Islamic banks. Religious obedience is a rational motivator like personal satisfaction because both of them both need information to base their consumption patterns. This is based on the scope of knowledge that gives a positive value to the consideration of prevailing social norms. Therefore, in socialization, persuasive alternative steps need to be taken. This method requires the involvement of religious, community and government elements.